Borrowing from the insurer: An empirical analysis of demand and impact of insurance in China - Liu, Yanyan; Chen, Kevin Z.; Hill, Ruth Vargas; Xiao, Chengwei (International Food Policy Research Institute, 2013)
Farmers in developing countries face relatively large income risk and have limited access to formal financial products that can help them manage their risk. We present results from a randomized controlled trial in rural China designed to understand whether a small change in the timing of a premium payment for a swine insurance contract helps to overcome an important barrier to insurance demand and, if so, whether the resulting increase in insurance would allow farmers to increase investment in activities that expose them to the risk being insured against. We find that insurance take-up is three times higher among those who were given the option to pay at the end of the insured period.